„Let Them Try to Figure It Out First“ – Reasons Why Experts (Do Not) Provide Feedback to Novice Programmers - Lohr, Dominic; Kiesler, Natalie; Keuning, Hieke; Jeuring, Johan (Proceedings of the 29th ACM Conference on on Innovation and Technology in Computer Science Education, 2024)
A recent ITiCSE working group investigated when and how experts give feedback and hints at steps novice programmers take when solving programming problems. Based on the feedback literature and an analysis of expert feedback on steps, the working group designed guidelines for when and how to give feedback. The feedback provided by educators using these guidelines on a number of sequences of student steps varied a lot. In this paper, we try to answer the question of why educators give feedback at particular steps to novice learners of programming. We prepared six authentic sequences of student steps when solving an introductory programming task. The preprocessed sequences were used in a survey to gather information about when and why an expert would give feedback. Respondents annotated each step from one sequence with if and why they would give feedback at that step. Our survey received 47 responses. We qualitatively analyzed the responses, resulting in a coding scheme consisting of 19 different reasons for why experts intervene (or not) when novice learners work on introductory programming tasks. We found a considerable variety of reasons experts give for when and how to help students with feedback and hints. Also, sometimes one expert uses a reason at a step to explain why they do intervene, and another expert uses the same reason at the step to not intervene. The categories of experts' feedback indicators will pave the way for several future studies and applications, including learning systems trying to resemble expert feedback strategies.<br
Keywords: Learning programming; expert feedback; feedback rationale; feedback guidelines; novice programmers